2019
DOI: 10.1111/jssr.12613
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Aging: Age and Cohort Effects and Their Implications for the Future of Religious Values in High‐Income OECD Countries

Abstract: It has long been noticed that older people tend to be more religious than younger people. However, it is still disputable whether this fact should be attributed to people generally becoming more religious with age per se (age effect), or to the process of secularization, wherein earlier cohorts (to which the now older people belong) used to be more religious than those that appeared later, younger cohorts (cohort effect). We try to distinguish between these two effects using a multifactor model applied to Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Regarding age, the findings revealed that older people were more likely to have more children than younger individuals. In addition to a longer life span, older people have been long acknowledged as having higher religiosity and greater conformity to religious values than younger people (Shulgin et al, 2019). Therefore, older individuals who complied with religious values encouraging pronatalist behaviors were more likely to have more children.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding age, the findings revealed that older people were more likely to have more children than younger individuals. In addition to a longer life span, older people have been long acknowledged as having higher religiosity and greater conformity to religious values than younger people (Shulgin et al, 2019). Therefore, older individuals who complied with religious values encouraging pronatalist behaviors were more likely to have more children.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by Corcoran, Pettinicchio & Robbins (2012) that belief in God will encourage moral behavior and discourage immorality. Shulgin, Zinkina & Korotayev (2019) concluded that the majority of OECD countries with high incomes had fewer religious individuals. Voas & Chaves (2016) argue that American religiosity has declined over the past several decades.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were informed about the aim of the research and were assured of anonymity and voluntary participation in the study. The research was cross-sectional due to the fact that the influence of the historical cohort was small (Shulgin, Zinkina, Korotayev, 2019;Bengtson, Silverstien, Putney, Harris, 2015). The authors used exploratory-critical interview on the development of religious morality in adults, which is based on Walesa's (2005) cognitive-developmental model of integral religiosity development.…”
Section: Methodsmentioning
confidence: 99%